Kelebihan Al-'Aqd di Kalangan Usahawan Francais Berlainan Agama - Mohd Huefiros Efizi Husain; Noor Naemah Abdul Rahman; Nor Fahimah Mohd Razif (USIM Press, 2024)
Vol. 5 No. 2 (2020): Jurnal Sains Insani